If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-5x + 35) + -1x + 7 = 0 Reorder the terms: 4(35 + -5x) + -1x + 7 = 0 (35 * 4 + -5x * 4) + -1x + 7 = 0 (140 + -20x) + -1x + 7 = 0 Reorder the terms: 140 + 7 + -20x + -1x = 0 Combine like terms: 140 + 7 = 147 147 + -20x + -1x = 0 Combine like terms: -20x + -1x = -21x 147 + -21x = 0 Solving 147 + -21x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-147' to each side of the equation. 147 + -147 + -21x = 0 + -147 Combine like terms: 147 + -147 = 0 0 + -21x = 0 + -147 -21x = 0 + -147 Combine like terms: 0 + -147 = -147 -21x = -147 Divide each side by '-21'. x = 7 Simplifying x = 7
| 5x/2-8=2x-7/6 | | 2s+7=-5s | | 10a-83=203 | | X=(18+8) | | x=(x)(x) | | 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 | | 9x+-9+9x= | | f(x-3)=5x^2-x-8 | | F(x)=5x^2+6x-8 | | -10.6x+5.6x=40 | | 18x-10-6w=50 | | -5(3d+8)=35 | | -4m+2-4m+12= | | 4(u-9)= |